On the Mathematical Modeling of Memristor, Memcapacitor, and Meminductor - Radwan, Ahmed G.; Fouda, Mohammed E.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book introduces the basic fundamentals, models, emulators and analyses of mem-elements in the circuit theory with applications. The book starts reviewing the literature on mem-elements, models and their recent applications. It presents mathematical models, numerical results, circuit simulations, and experimental results for double-loop hysteresis behavior of mem-elements. The authors introduce a generalized memristor model in the fractional-order domain under different input and different designs for emulator-based mem-elements, with circuit and experimental results. The basic concept of memristive-based relaxation-oscillators in the circuit theory is also covered. The reader will moreover find in this book information on  memristor-based multi-level digital circuits, memristor-based multi-level multiplier and memcapacitor-based oscillators and synaptic circuits.
Introduction -- Memristor: Models, Types and Applications -- Memristor Mathematical Models and Emulators -- Memristor-based Relaxation Oscillator Circuits -- Memristor-based Multilevel Digital Systems -- Memcapacitor: Modelling, Analysis and Emulators -- Memcapacitor based applications -- Meminductor: Modelling, Analysis and Emulators.
Keywords: Electronic circuits; Statistical physics; Information theory; Circuits and Systems; Applications of Nonlinear Dynamics and Chaos Theory; Information and Communication, Circuits